2022
DOI: 10.1590/1413-81232022272.44342020
|View full text |Cite
|
Sign up to set email alerts
|

Uso de hormônios não prescritos na modificação corporal de travestis e mulheres transexuais de Salvador/Bahia, Brasil

Abstract: Resumo O objetivo deste artigo é analisar o uso de hormônios não prescritos entre travestis e mulheres transexuais (TrMT) na cidade de Salvador, Bahia, Brasil. Trata-se de um estudo de corte transversal onde se utilizou a metodologia RDS (respondent driven sampling) para recrutar TrMT entre 2014 e 2016, em Salvador e sua Região Metropolitana. Foi realizada uma análise comparativa entre condições sociodemográficas, comportamentais e de afirmação de gênero com o uso de hormônios. Os dados ponderados pelo estimad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
4
0
3
Order By: Relevance
“…Furthermore, among the other mentioned medications, antidepressants were the most commonly used in this study. These findings align with a study conducted in a city in southern Brazil, where 77% of transgender individuals reported using psychotropic drugs, particularly selective serotonin reuptake inhibitors (SSRIs) as the most commonly used medication for depressive symptoms 27 . Difficulties in access, discrimination, and unmet expectations in public healthcare are among the contributing factors to the development of depression.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, among the other mentioned medications, antidepressants were the most commonly used in this study. These findings align with a study conducted in a city in southern Brazil, where 77% of transgender individuals reported using psychotropic drugs, particularly selective serotonin reuptake inhibitors (SSRIs) as the most commonly used medication for depressive symptoms 27 . Difficulties in access, discrimination, and unmet expectations in public healthcare are among the contributing factors to the development of depression.…”
Section: Discussionsupporting
confidence: 86%
“…It is worth noting that although the previously mentioned study by Silva et al 27 is almost equivalent to the present study in terms of the number of participants, their sample focused only on transgender women and travesties, which may explain the high prevalence of hormone use. While feminizing hormones require a medical prescription, they are more easily obtained compared to androgens.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…E por que não tiveram orientações da equipe? A literatura mostra uma procura pelo processo sem orientação se dá muitas vezes pela dificuldade de encontrar profissionais da saúde especializados e pela escassez de serviços (SILVA RA et al, 2022;BRASIL, 2015).…”
Section: Sim Nãounclassified
“…The living and health conditions of this group have promoted the development of studies in Brazil 27 , 28 , including in São Paulo 26 , 29 . Aiming to expand the knowledge about the characteristics and needs of TrTGW, TransAmigas project innovated by providing a personalized and culturally targeted intervention for this group, using as a reference the gender affirmative model, developed by Sevelius et al 30 (p. S65), which defines gender affirmation as “ an interpersonal, interactive process whereby a person receives social recognition and support for their gender identity and expression ”.…”
Section: Introductionmentioning
confidence: 99%